A Nexus among Reliability Improvement of Distribution System with Optimal Placement and Capacity of Wind-Based Distributed Generation Management - Syahrial Shaddiq (Universitas Teknokrat Indonesia, 2021)
Along with the world population growth, the need for a source of electrical energy is higher, so a reliable system with higher capacities is expected. Renewable energy becomes an alternative that supports the goal of reducing the risk of disruption, thus increasing the distribution system’s reliability. A lot of industries and public settlement uses renewable sources of energy as an alternative power supply to comply their energy needs. This research uses wind turbine as a source of renewable energy in the distributed generation (DG). However, the required investment in wind-based DG is commonly considered too costly to deploy and require a proper planning on its placement method. The flower pollination algorithm (FPA) method could be a solution to achieve optimal placement of wind-based DG, thus increase the distribution system’s reliability, which is indicated by minimum energy not supplied (ENS) index.